2021
DOI: 10.1016/j.cropro.2020.105335
|View full text |Cite
|
Sign up to set email alerts
|

An outlook on wheat health in Europe from a network of field experiments

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
0
10
0
5
Order By: Relevance
“…However, at the sites in Söllingen and Dahnsdorf, clear infections appeared at the end of the growing season in 2017 and 2018. Septoria leaf blotch is one of the most important diseases in Europe, as it is in Germany, and lack of control can lead to high yield losses (Jahn et al, 2012;Willocquet et al, 2021). The severe yellow rust epidemic masked the Septoria leaf blotch symptoms on the leaves to some extent in the years studied and at the same time the weather conditions were not always optimal for further Septoria infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, at the sites in Söllingen and Dahnsdorf, clear infections appeared at the end of the growing season in 2017 and 2018. Septoria leaf blotch is one of the most important diseases in Europe, as it is in Germany, and lack of control can lead to high yield losses (Jahn et al, 2012;Willocquet et al, 2021). The severe yellow rust epidemic masked the Septoria leaf blotch symptoms on the leaves to some extent in the years studied and at the same time the weather conditions were not always optimal for further Septoria infections.…”
Section: Discussionmentioning
confidence: 99%
“…needs to be investigated. The use of simulation models may serve to supplement the limited data on crop yield losses caused by pests and pathogens, to scale them up, and to evaluate scenarios on future or changed climatic, production, and cropping system conditions [231]. Process-based crop models, such as DSSAT-CROPSIM, simulate the soil-plant-atmosphere system, including abiotic stress due to water and nutrient deficiency.…”
Section: Mineral-ecological Cropping Systems From the Perspective Of Yield And Product Qualitymentioning
confidence: 99%
“…Winter wheat leaf diseases is a considerable risk factor of wheat production; therefore, it is necessary to understand importance of agronomic practice on the development of this disease. It is found that leaf blotches are the dominant leaf diseases across Europe (Willocquet et al, 2020). Tan spot, caused by Pyrenophora tritici-repentis and Septoria leaf blotch caused by Zymoseptoria tritici are the most important wheat leaf diseases in many regions of wheat cultivation, including Uruguay, Canada, Baltic region etc.…”
Section: Introductionmentioning
confidence: 99%